(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
A B-spline Quasi-interpolation Empirical Mode Decomposition (BSQI-EMD) method is presented and applied to similarity analysis of DNA sequences. The B-spline quasi-interpolation is used to approximate the extrema envelopes during the Intrinsic Mode Function (IMF) sifting process. The BSQI-EMD method is simple, easy to implement, and does not require solving any linear system of equations. Then we implement the classic EMD method and our method respectively. This work verifies our method's suitability and better performance for similarity/dissimilarity analysis among the coding sequences of the first exon of 03b2-globin gene of ten different species.